An interesting case of retrocaecal internal herniation causing small bowel obstruction - Hassan N.H.M.; Zakaria Z.; Ismail M.A.T.; Henry F.; Jailani R.F. (Surgical Society of Northern Greece, 2024)
Indexed by Scopus